The effects of the different crude protein levels on some blood metabolites in fattening türkgeldi male lambs - I. Yaman Yurtman; Şafak Polatsü; Ensar Başpınar; M. Levent Özdüven (Eurasian Journal of Veterinary Sciences)
In this study. Ihe effects of the raiton crude protein (CP) level on some blood metabolites were investigated in fattening Tükgeldi male lambs. For this purpose 3 isocaloric compound feeds were prepared which their CP contents were 148.7 g/kg DM. 162.2 g/kg DM and 174.8 g/kg DM respectively 100 g/Head day dried hay and ad-libitum compound teed were given individually to the lambs as feeding regime during 56 days. The experiment was carried out on 3 groups (n=6) and blood samples were collected at 0, 14, 28. 42 and 56th days of the trial The analysis of glucose, total protein, urea, uric acid, creatinin, albumin, A/G ratio, triglicerid, cholesterol. Ca. P, Na, K quantities and ALP, GGT, AST and ALT activities were done on serum. At the end of the experiment only significant effects of the given differences of CP levels were found on serum urea and total serum protein levels (P<0.05).